Theoretical foundations of Islamic banking and its current place in the world economy - S. A. Pshibieva (Путеводитель предпринимателя)
The research is aimed at studying the basic principles of Islamic banking and its modern distribution. This paper analyzed the development of Islamic banking in the world: in the Arab countries, Europe, the CIS countries and Russia.